2001
DOI: 10.1038/sj.bmt.1703285
|View full text |Cite
|
Sign up to set email alerts
|

Double lumen port access in patients receiving allogeneic blood stem cell transplantation

Abstract: Summary:We performed a prospective trial investigating the feasibility of a double lumen port access in 26 patients with hematological malignancies or solid tumors receiving either standard conditioning (n ‫؍‬ 9, median age 49 years (range 19-65)) or dose-reduced conditioning (n ‫؍‬ 17, median age 56 years (range 35-66)) followed by allogeneic blood stem cell transplantation. The port system was implanted within 3 months (n ‫؍‬ 20, range 7-91 days) before transplantation or as indicated at different time point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…There is no well-defined platelet count threshold for patients receiving a single-or doublelumen PORT, despite the fact that bleeding complications have been reported after PORT placement [10,13,19]. However, it is considered that major invasive procedures can be performed safely in patients with a platelet count of 40-5010 9 /l [22].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…There is no well-defined platelet count threshold for patients receiving a single-or doublelumen PORT, despite the fact that bleeding complications have been reported after PORT placement [10,13,19]. However, it is considered that major invasive procedures can be performed safely in patients with a platelet count of 40-5010 9 /l [22].…”
Section: Discussionmentioning
confidence: 93%
“…A single-lumen PORT is widely used in patients with solid tumours [1], and these PORTs have also been used in patients with AL during induction chemotherapy [12]. However, there is only limited experience of double-lumen PORTs in patients with haematological malignancies [19].…”
mentioning
confidence: 99%
“…Four studies did not report the medical specialty of the inserter [12,43,50,61]. Although all studies reported functional outcomes, most focused on the insertion technique and complications of CPs (n=24) [4-6, 8, 15, 18, 20, 25-27, 29, 32, 38, 40-43, 45-47, 51, 59-61] or APs (n=11) [7, 9, 12, 16, 19, 33-35, 37, 48, 54].…”
Section: Characteristics Of Selected Articlesmentioning
confidence: 96%
“…The number of longterm CVC-associated bacteraemia per 1,000 catheter days in patients with haematological malignancies or solid tumours ranges between 3.0 and 8.4 [9,13,24]. The corresponding number in patients with a PORT ranges between 0.05 and 3.9 [1,2,9,20,24]. Thus, the PORT seems to be associated with a lower rate of catheter-related infections than the CVC.…”
Section: Introductionmentioning
confidence: 97%
“…The CVC has since then been elaborated and improved regarding material, shape and number of lumens. Various types of CVADs are currently available, and in patients requiring extensive intravenous therapy and frequent blood sampling the long-term CVC and the totally implantable subcutaneous port system (PORT) are commonly used [9,20,24].…”
Section: Introductionmentioning
confidence: 99%